TISSUE ENGINEERING IN MAXILLOFACIAL BONE RECONSTRUCTION: TISSUE ENGINEERING IN MAXILLOFACIAL BONE RECONSTRUCTION - Kamadjaja, David (Journal of Stem Cell Research and Tissue Engineering, 2017)
Maxillofacial bone defects due to tumor resection, trauma or infections should be reconstructed to maintain the bone continuity in order to preserve its masticatory, speech and esthetic functions. Autogenous bone graft have been the gold standard for mandibular defects reconstruction, however, it is associated with limitation in volume and availability as well as the donor site morbidities. Tissue engineering approach has been proved to be a good alternative to overcome the limitation of autogenous bone graft. Tissue engineering studies have been conducted combining various sources of mesenchymal stem cell, scaffolds, and or signaling molecules. The paper aims to provide information on the development of bone tissue engineering researches to reconstruct bone defects through results of numerous studies obtained in the English literature. As the conclusion, bone tissue engineering is a potential approach to reconstruct maxillofacial bone defects.